HOME SMART (HS) MENGGUNAKAN MIKROKONTROLER BERBASIS ESP8266 DAN IoT (INTERNET of THINGS) - Achmad Setio Prabowo; Ayub Wimatra (LPPM Politeknik LP3I Medan, 2019)
IoT (Internet of Things) has become a separate field of research since the development of internet technology and other communication media, the more human needs are developing about technology, the more research that will be present, the internet of things is one of the thoughts of researchers who optimize several tools such as media sensors, radio frequency identification (RFID), wireless sensor networks and other smart objects that allow humans to easily interact with all equipment connected to the internet network. This paper describes the design of room control systems that utilize the IoT concept as a means for controlling and monitoring Avionic laboratory rooms via wifi in realtime. This helps the laboratory staff and AMTO managers in controlling lighting and monitoring temperature, humidity and smoke in the avionics lab room even though they are not in the laboratory location so as to increase the utility of the equipment.